A computational framework with an adaptive mesh refinement technique for concentrated suspension flows. (2nd October 2020) - Dbouk, Talib
Abstract: A computational framework (solver) is developed for incompressible isothermal concentrated non-colloidal suspension flows of rigid particles. The number of particles can be of the order of millions. The developed solver, named "SuspensionFoam" can predict the phenomenon of shear-induced migration in complex geometries in a continuum mechanics modeling approach. It employs the C++ object-oriented OpenFOAM library features including adaptive mesh refinement (AMR), dynamic mesh rotation in both 2D and 3D, adaptive time steps, multi-CPU parallel-run over MPI (and open MPI) and run-time selection of different liquid and particles properties (i.e. diameter, maximum packing). Three different numerical examples have been conducted by simulating isodense suspension flow in a vertical Couette cell, non-isodense resuspension and mixing of particles in a horizontal Couette cell, and isodense suspension flow in a conduit. The present AMR technique is found to reduce the computational process considerably, with a good accuracy. Numerical results are presented and discussed, with comparisons to experimental data.